Genome Sequence of the Obligate Gammaproteobacterial Methanotroph Methylomicrobium album Strain BG8 - Kits, K. Dimitri (American Society for Microbiology, 2013)
The complete genome sequence of Methylomicrobium album strain BG8, a methane-oxidizing gammaproteobacterium isolated from freshwater, is reported. Aside from a conserved inventory of genes for growth on single-carbon compounds, M. album BG8 carries a range of gene inventories for additional carbon and nitrogen transformations but no genes for growth on multicarbon substrates or for N fixation.